Finite nuclear size corrections to the recoil effect in hydrogenlike ions. (28th May 2015) - Aleksandrov, I A; Shchepetnov, A A; Glazov, D A; Shabaev, V M
Abstract: The finite nuclear size corrections to the relativistic recoil effect in H-like ions are calculated within the Breit approximation. The calculations are performed for the 1s, 2s, and 2p1/2 states in the range Z = 1–110. The obtained results are compared with previous evaluations of this effect. It is found that for heavy ions the previously neglected corrections amount to about 20% of the total nuclear size contribution to the recoil effect calculated within the Breit approximation.